Spontaneous legal socialization and legal education: the verge of correlation - Скуріхін, Сергій Миколайович; Skurikhin, Serhii M.; Скуріхін, С. М.; Skurikhin, S. M. (Одеса : Гельветика, 2019)
У статті розглянуто варіанти співвідношення правової соціалізації і правового виховання. Запропоновано розуміння правового виховання як частини правової соціалізації. Виділено основні грані співвідношення стихійної й цілеспрямованої (правове виховання) правової соціалізації.

The article deals with variants of the correlation of legal socialization and legal education. An understanding of legal education as part of legal socialization is offered. The main features of the elemental and purposeful (legal upbringing) legal socialization are highlighted. Special attention is paid to the analysis of the strategic goals of these phenomena. It is concluded that if the purpose of legal education is the formation of a legal culture, then the purpose of legal socialization of the individual, its key task is the formation of individual legal experience.
Skurikhin S. M. Spontaneous legal socialization and legal education: the verge of correlation / S. M. Skurikhin // Юридичний вісник. - Одеса : Гельветика - 2019. - № 1. - С. 60-65.
Keywords: legal socialization; legal education; legal culture; legal experience; aims of legal education; goals of spontaneous legal socialization; правова соціалізація; право на освіту; правова культура; юридичний досвід; юридична освіта; спонтанна правова соціалізація; Research Subject Categories::LAW/JURISPRUDENCE